2010
DOI: 10.1007/s11046-010-9330-5
|View full text |Cite
|
Sign up to set email alerts
|

Building-Associated Neurological Damage Modeled in Human Cells: A Mechanism of Neurotoxic Effects by Exposure to Mycotoxins in the Indoor Environment

Abstract: Damage to human neurological system cells resulting from exposure to mycotoxins confirms a previously controversial public health threat for occupants of water-damaged buildings. Leading scientific organizations disagree about the ability of inhaled mycotoxins in the indoor environment to cause adverse human health effects. Damage to the neurological system can result from exposure to trichothecene mycotoxins in the indoor environment. This study demonstrates that neurological system cell damage can occur from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Controlling their accumulation in small grains remains a huge challenge. Trichothecenes cause growth retardation, hemorrhagic lesions, immune dysfunction, and emesis (2,3) and are neurotoxic (4)(5)(6). Trichothecene poisoning causes acute gastroenteritis and has been linked to alimentary toxic aleukia (ATA) and Kashin-Beck disease, an endemic and chronic degenerative osteoarthritis (3).…”
mentioning
confidence: 99%
“…Controlling their accumulation in small grains remains a huge challenge. Trichothecenes cause growth retardation, hemorrhagic lesions, immune dysfunction, and emesis (2,3) and are neurotoxic (4)(5)(6). Trichothecene poisoning causes acute gastroenteritis and has been linked to alimentary toxic aleukia (ATA) and Kashin-Beck disease, an endemic and chronic degenerative osteoarthritis (3).…”
mentioning
confidence: 99%
“…Individual mycotoxins differ in their toxic effects on organisms. Admittedly, they deteriorate the immune system and exhibit carcinogenic, mutagenic, embryotoxic, teratogenic, haemorrhagic, dermatotoxic, cytotoxic, neurotoxic activity, they also impair fertility [19][20][21][22][23]. Toxinogenic activity of individual species of molds is a property that becomes apparent in specific conditions of the substrate's humidity, temperature, availability of nutrients, and the presence of other (competitive) fungi [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Trichothecene mycotoxins cause multisystemic effects including nervous disorders, cardiovascular alterations, and immunosuppression [236]. A study investigating Satratoxin A exposure demonstrated that the toxin produces neuropathology at levels that occur in water-damaged buildings [237]. Trichothecenes and many other mycotoxins can bind to ribosome subunits generating Bribotoxic stress^which leads to the p38, c-Jun N-terminal kinase (JNK), ERK, and MAPK activation [238][239][240].…”
Section: Chronic Mold and Mycotoxin Exposurementioning
confidence: 99%
“…Saratoxin H exposure leads to the activation of MAPKs, JNK p38, and capase-3 together with the predictable development of oxidative stress, increased levels of reactive oxygen species, and the depletion of reduced glutathione [250]. There is evidence that the constant presence of Saratoxin H with subsequent self-amplifying neuroinflammation and chronic immune activation renders an individual more susceptible to the effects of other neurotoxic species in the environment and more susceptible to the presence of such species in the environment thereafter [237,306]. This would be consistent with evidence demonstrating temporal exacerbation of neurotoxicity via microglial priming [21].…”
Section: Chronic Mold and Mycotoxin Exposurementioning
confidence: 99%